Enantioselective syntheses of (-)-pinellic acid, alpha- and beta-dimorphecolic acid - Baruah, Pranjal K.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Tetrahedron, 2007)
An efficient enantioselective convergent approach for the synthesis of (-)-pinellic acid 1, alpha- and beta- dimorphecolic acid (2 and 3) from 1,9-nonane diol is described. The synthetic strategy features Sharpless asymmetric hydroxylation, Sonogashira coupling and Birch reduction. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: asymmetric dihydroxylation; influenza; Sonogashira coupling

Enforcing periodic secondary structures in hybrid peptides: a novel hybrid foldamer containing periodic gamma-turn motifs - Baruah, Pranjal K.; Sreedevi, N. K.; Gonnade, Rajesh G.; Ravindranathan, Sapna; Damodaran, Krishnan; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2007)
{This note describes the design, synthesis, and conformational studies of a novel hybrid foldamer that adopts a definite compact, three-dimensional structure determined by a combined effect of the special conformational properties of the foldamer constituents. The striking feature of this de novo designed foldamer is its ability to display periodic gamma-turn conformations stabilized by intramolecular hydrogen bonds. Conformational investigations by single-crystal X-ray studies, solution-state NMR, and ab initio MO theory at the HF/6-31G*
Keywords: ammonia-TPD; benzylation reaction; Ce-Al-MCM-41; Friedel-Crafts alkylation; pyridine-FrIR

Expanding the structural repertoire of beta/alpha Ant-Pro (anthranilic acid-proline) oligomers into gamma/alpha 2-Amb-Pro (2-aminomethyl benzoic acid-proline) oligomers - Ramesh, Veera V. E.; Priya, Gowri; Rajamohanan, P. R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Tetrahedron, 2012)
In this article, we report a novel class of heterogeneous synthetic oligomers featuring the conformationally constrained amino acid residues - 2-aminomethyl benzoic acid (2-Amb) and proline (Pro) in repeating sequences. Oligomers as large as hexadecamers featuring the conformationally restricted gamma/alpha 2-Amb-Pro motif have been assembled using solution-phase Boc strategy, following multi-step synthetic sequences starting from the commercially available O-toluic acid. EDC-mediated peptide coupling has been found to be optimum for the assembly of the relatively non-polar oligomers, which could be readily purified by the standard column chromatographic purification procedures. This study offers considerable prospects of expanding the structural repertoire of beta/alpha Ant-Pro motif, which has been described earlier to assume right-handed helical architecture displaying robust nine-membered-ring closed network of hydrogen-bonding interactions, into gamma/alpha 2-Amb-Pro motif. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Amino acids; Foldamer; Peptides; Proline; Synthetic oligomers

Easy and multigram-scale synthesis of pillar[5]quinone by the hypervalent iodine oxidation of 1,4-dimethoxypillar[5]arene - Shivakumar, Kilingaru I.; Sanjayan, Gangadhar J. (Synthesis-Stuttgart, 2013)
Pillar[5]quinone (P[5]Q), a potential molecule for anion recognition and supramolecular host-guest chemistry, has not as yet been used for practical purposes, presumably due to the synthetic difficulties in obtaining it in large amounts. Herein, we reveal an easy-to-operate and chromatography-free synthetic strategy that can furnish P[5]Q on a multigram scale; its success relies on the utility of hypervalent iodine, generated in situ from Oxone/ iodobenzene, as an efficient oxidant. Pillar[5]quinone was obtained in multigram quantities by oxidation of 1,4-dimethoxypillar[5]arene with Oxone/iodobenzene and simple purification by crystallization from 1,1,2,2-tetrachloroethane, thus opening up the opportunity to explore the properties of this interesting macrocyclic quinone.
Keywords: hypervalent iodine oxidation; macromolecules; pillar-arenes; supramolecular chemistry

Ester vs. amide on folding: a case study with a 2-residue synthetic peptide - Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Gawade, Rupesh L.; Kotmale, Amol S.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
Although known for their inferiority as hydrogen-bonding acceptors when compared to amides, esters are often found at the C-terminus of peptides and synthetic oligomers (foldamers), presumably due to the synthetic readiness with which they are obtained using protected peptide coupling, deploying amino acid esters at the C-terminus. When the H-bonding interactions deviate from regularity at the termini, peptide chains tend to ``fray apart''. However, the individual contributions of C-terminal esters in causing peptide chain end-fraying goes often unnoticed, particularly due to diverse competing effects emanating from large peptide chains. Herein, we describe a striking case of a comparison of the individual contributions of C-terminal ester vs. amide carbonyl as a H-bonding acceptor in the folding of a peptide. A simple two-residue peptide fold has been used as a testing case to demonstrate that amide carbonyl is far superior to ester carbonyl in promoting peptide folding, alienating end-fraying. This finding would have a bearing on the fundamental understanding of the individual contributions of stabilizing/destabilizing non-covalent interactions in peptide folding.

Exploiting powder x-ray diffraction to establish the solvent-assisted solid-state supramolecular assembly of pillar[5]quinone - Shivakumar, Kilingaru I.; Yan, Yuncheng; Hughes, Colan E.; Apperley, David C.; Harris, Kenneth D. M.; Sanjayan, Gangadhar J. (Crystal Growth & Design, 2015)
We report the solvent-mediated supramolecular assembly of pillar[5]quinone (P[5]Q), a symmetric cyclamer containing five benzoquinone moieties bridged by five alternating methylene units. The supramolecular assembly of P[5]Q is shown to be facilitated by 1,1,2,2-tetrachloroethane (TCE) as solvent, producing a microcrystalline solvate material P[5]Q(.)2TCE with a fluffy texture. Optical and electron microscopy reveal that this material has a rod-shaped morphology, extending to several micrometers in length. Due to the microcrystalline nature of the material, structure determination was carried out directly from powder X-ray diffraction data, augmented by high-resolution solid-state C-13 NMR. The two crystallographically distinct TCE molecules occupy different types of void in the structure and have different dynamic properties. Crystallization of P[5]Q was attempted from a large number of different solvents, but only TCE was found to facilitate the formation of a crystalline phase. Indeed, features of the crystal structure suggest that the TCE component plays an important role in promoting the columnar assembly of P[5]Q molecules.

Exploring the gem-dimethyl effect in the formation of imine-based macrocycles and cages - Madhu, Suresh; Rashmi, E. V.; Gonnade, Rajesh Ghanshyam; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2017)
Using the gem-dimethyl effect as a platform, a variety of organic [2+2] macrocycles and [2+3] cofacial cages was obtained in high yields. Imine-based macrocyclization could be performed even at high concentrations (0.5 to 1.0 M), via instant mixing of aldehydes and amines.

Efficient and convenient route for the synthesis of thiophene-2-carboxamidines as potential inhibitors of nitric oxide synthase (NOS) - Rashid, P. P.; Singh, Dharmendra; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2019)
A mild and efficient synthesis of substituted thiophene-2-carboxamidines which are potent inhibitors of nitric oxide synthase (NOS) is reported herein. The key step involves reaction of a BOC-protected imidazolyl thiophene-2-carboxamidine reactive intermediate with various primary amines to form BOC-thio-phene-2-carboxamidines which could be readily deprotected using TFA to furnish free carboxamidines. The method is very mild and tolerates diverse substituents including sensitive peptide and amino acid fragments. This new methodology represents a substantial improvement to the literature method owing to its simplicity and hassle-free purification procedures. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Amidines; Nitric oxide synthase (NOS); Nitric oxide synthase inhibitors; Thiophene-2-carboxamidines